Solution processed thin film deposition of CZTS for solar cell applications - Kong, Ren Hwai (2015)
CZTS (Cu2ZnSnS4) is a potential alternate material for CIGS (CuInxGa1-xSe) solar cell for its abundant material source. Ball milling and screen printing were studied to fabricate CZTS cell. Two types of precursors, sulfide (CuS, ZnS and SnS) and metal (Cu, Zn and Sn) powders were ball milled and fabricated into screen printing pastes. The effect of milling parameters on cell performance was also explored. After screen printing on Molybdenum-sputtered soda lime glass, the precursor films were sent for heat treatment to form CZTS. The best device was made from metal precursor (with low milling speed and short duration) and the measured efficiency was 1.72%, which is about 3 times higher than screen printed CZTS cell found in literature (0.49%). The significant improvement of short circuit current density is achieved by forming denser and more crystalline film structure, revealed from SEM images. XRD results confirmed the phase transformation after heat treatment but EDX results showed significant elemental composition changes, which is not favored. Future works should include Raman Spectroscopy to investigate possible secondary phases. Our researches have demonstrated that screen printing could be a possible low cost fabrication method for CZTS cell.